The determinants influencing bilingual instruction in Chinese higher education: a complex network analysis - Kun Cheng; Xin Cheng; Wenya Wang (Humanities & Social Sciences Communications, 2024)
Abstract The primary objective of this research was to investigate the determinants influencing bilingual instruction at the tertiary level in the Chinese educational context. A complex network analysis was adopted for this study. Twenty-one factors were first identified using the Delphi method, a qualitative research method. A complex network was then designed for analysis of the factors. The results indicate that the network is a scale-free network with certain key factors. The findings further reveal that the subject language feature and bilingual instruction models have more connections with other factors, and thus they are the most significant factors to ensure the effective implementation of bilingual instruction. The findings of this research may provide implications for bilingual education.